Optimizing Development in Research-Based Villages by Utilizing ADD - Boby Indra Prayoga (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The village which is the smallest government territory in the Unitary State of the Republic of Indonesia, in the current era of government becomes one of the priorities of acceleration of development, with funds disbursed from APBN and combined with APBD which is channeled through Village Funds Fund (ADD) program, Will accelerate the process of development in the village, and indirectly will occur even distribution of development which would have an impact on improving the welfare of rural communities. Can we imagine when the development is done in every village simultaneously throughout Indonesia, of course, the process of economic cycle is high enough, and accelerate the process of development implementation needed by the village community, unlike the previous system which if a village wants to propose the development must go through Stage Musrembang in the village until the center of the center, of course, a very long journey process. But with the current central government program will make it easier for the community to build their village. The establishment of a government in the village is of course based on interregional regulation is the Village Law which is a set of rules concerning the administration of village government, with consideration has evolved in various forms so it needs to be protected and empowered to be strong, advanced, independent and democratic so as to create a foundation Strong in implementing governance and development towards a just, prosperous and prosperous society. The Act also regulates material on the Principles of Arrangement, Status and Types of Villages, Village Arrangements, Village Authorities, Village Governance, Village Villagers' Rights and Obligations, Village Regulations, Village Finance and Village Assets, Rural Development and Rural Area Development, Village Owned Enterprises, Village Cooperation, Village Community Institutions and Village Customary Institutions, as well as Guidance and Supervision. In addition, the Act also regulates with special provisions that apply only to “Desa Adat” as set forth in Chapter XIII. One of the most crucial points in the discussion of the Village Bill is related to the budget allocation for the village, in the elucidation of Article 72 Paragraph 2 on Village Finance. The amount of direct budget allocations to villages is set at 10 per cent from and outside of regional transfers. Then considered the population, poverty, area, geography difficulties. This is in order to improve the village community because it is estimated that each village will get funding of about 1.4 billion based on the calculation in the explanation of the village law that is, 10 percent of the regional transfer funds according to APBN for the village apparatus of Rp. 59, 2 trillion, coupled with funds from the APBD of 10 percent about Rp. 45.4 trillion. The total funding for the village is Rp. 104, 6 trillion to be divided into 72 thousand villages in Indonesia. It is conceivable that such funds can be utilized properly in the right way and the right target, then the distribution of development will be quickly realized so that the impact on improving the welfare of the community.